1973
DOI: 10.1104/pp.51.4.749
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound Adenosine Triphosphatase Activities of Oat Roots

Abstract: Homogenates of oat (Arena satira cv. Goodfield) roots contained at least five membrane-associated adenosine triphosphatase (ATPase) activities. The membrane-bound ATPases were separated on sucrose gradients and distinguished by membrane density, pH optima, sensitivity to monovalent salts, and substrate specificity.A membrane fraction sedimenting at low centrifugal force (13,000g) contained two ATPase activities at pH 9.0. One membrane ATPase was coincident with cytochrome c oxidase activity and had a density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…The distribution of enzyme activities in fractions prepared according to Scheme A are given in Table I. The highest specific activity of Mg2+-ATPase at pH 5.5 ATPases FROM I KCl-stimulated ATPase are lower than those found in oat root membrane fractions (6,10,12), they are comparable to previously reported values for the activity of this enzyme in maize root membrane fractions (4,11,17,24).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The distribution of enzyme activities in fractions prepared according to Scheme A are given in Table I. The highest specific activity of Mg2+-ATPase at pH 5.5 ATPases FROM I KCl-stimulated ATPase are lower than those found in oat root membrane fractions (6,10,12), they are comparable to previously reported values for the activity of this enzyme in maize root membrane fractions (4,11,17,24).…”
supporting
confidence: 82%
“…The properties of the ATPase found in the light Ficoll fraction implicated it in ion transport (24). Leonard et al (10) also found a small peak of KCIstimulated ATPase activity from oat roots at low buoyant densities but regarded it as less significant than the activity associated with the plasmalemma.…”
mentioning
confidence: 99%
“…The rate of ATP-hydrolysis by plant MgATPases is dependent upon the presence of Mg ions and is stimulated by the presence of KCI (10,11). Figure 3 (10,18).…”
Section: Methodsmentioning
confidence: 99%
“…The surprising finding is that respiration occurs at 50%o of the control rates after a 24-hr (Table IV) which has previously been correlated with K+ uptake (6). This ATPase is bound to a membrane fraction; one component of this fraction is the plasmalemma (15). In animal cells I mM Cd2+ inhibited mitochondrial ATPase and plasma membrane ATPase to 70% of control rates and after a 2 mm Cd2" treatment, 50% of control rates remained (17).…”
mentioning
confidence: 96%
“…The (15). The membrane pellet (13,000-80,000g) was suspended in 0.25 M sucrose and assayed according to the procedure of Leonard et al (15) at 30 C (pH 6) with Tris-ATP, in the presence or absence of I mm CdSO4. Potassium Uptake.…”
mentioning
confidence: 99%